Analisis faktor-faktor yang mempengaruhi independensi akuntan publik dalam pelaksanaan audit (study survey pada kantor akuntan publik di pekanbaru dan batam) - Kirana Putri; Hardi '; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to analyze the influences of independency in appearance of public accountant which consist of some variables, such as monetary, tying importance factor and relation of effort with client, office public accountant size, measure the duration or assignation of audit, emulation between office public accountant and audit of fee to independency of public accountant.This research applied on public accountant offices in Batam and Pekanbaru. The methode of research is surveilance methode by sending direct and indirectly quistionaires. The results of f-test showed that all independent variables influenced the dependent variables. The results of t-test showed that monetary, tying importance factor and relation of effort with client, the duration or assignation of audit, and audit of fee had a significant effect to independency appearance of public accountant. The R2 effect by all independent variables are 64.2%, and 35.8% influenced by other variables.Keywords: independency, public accountant, audit fee .